2018
DOI: 10.3390/rs10121902
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Camera High-Speed Videogrammetry for Three-Dimensional Measurement of Laminated Rubber Bearings Based on the Large-Scale Shaking Table

Abstract: Laminated rubber bearings are widely used for the mitigation of seismic damage of large-scale structures and equipment. However, owing to the flexibility in horizontal direction, the traditional contacted transducer is difficult to acquire the displacement data accurately in the three directions, respectively. In this paper, three-dimensional displacement measurement of laminated rubber bearing based on the large-scale shaking table is achieved by the use of a tri-camera high-speed videogrammetric system consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This method was chosen since the wall being tested lacked the texture (Figure 2a) to carry out either the photogrammetric approach based on digital image correlation or the structure from motion strategy. To this end, a similar strategy as proposed by Tong et al [24,25] was used, in which an edge detection algorithm was used to estimate the edges of the targets, followed by a minimization strategy based on the Levenberg-Marquardt method, to estimate the center of the targets. Instead of using a morphological edge detector, our strategy employs state-of-the-art edge detectors based on the partial area effect proposed by Trujillo et al [36].…”
Section: Photogrammetric Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was chosen since the wall being tested lacked the texture (Figure 2a) to carry out either the photogrammetric approach based on digital image correlation or the structure from motion strategy. To this end, a similar strategy as proposed by Tong et al [24,25] was used, in which an edge detection algorithm was used to estimate the edges of the targets, followed by a minimization strategy based on the Levenberg-Marquardt method, to estimate the center of the targets. Instead of using a morphological edge detector, our strategy employs state-of-the-art edge detectors based on the partial area effect proposed by Trujillo et al [36].…”
Section: Photogrammetric Approachmentioning
confidence: 99%
“…In addition to this, its flexibility makes it possible to evaluate the deformation suffered by different engineering solutions, from small scales (e.g., mechanical tests) [16,[21][22][23]] to large structures [7,14,15,20]. This property of the ability to capture several images per second makes it possible to use this technology in dynamic scenarios (e.g., shaking table tests) [7,14,17,20,[24][25][26][27]. Within this discipline, there are three strategies that are commonly applied in order to evaluate the changes that occur during a scenario: (i) digital image correlation method (DIC) [10][11][12]16]; (ii) structure from motion approach using change detection algorithms (i.e., cloud-to-cloud comparison algorithms) [15,[28][29][30]; and (iii) point-tracking approaches [14,20,23,25,26,31].…”
mentioning
confidence: 99%
“…Videogrammetry is one such method that utilizes two or more high-speed industrial cameras placed at different positions to monitor fast-moving objects simultaneously. Through captured image sequences, videogrammetry can accurately calculate the three-dimensional (3D) spatial coordinates of the measured object in each epoch [7]. Prior studies have demonstrated the ability of videogrammetry to achieve sub-millimetre accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Vision-based methods are becoming crucial in the non-contact measurement of displacement and velocities of engineering structures [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, the use of special high-speed imaging technology is necessary if the dynamic response contains high frequencies, which cameras cannot correctly capture with standard frame rates.…”
Section: Introductionmentioning
confidence: 99%
“…A Phantom high-speed camera with a maximal frame rate of 12,800 fps was used in the investigation. Tong et al [ 15 ] described a videogrammetry method for three-dimensional vibrations reconstruction of a structure excited on a large-sized shaking table. The tests were carried out to examine the behavior of laminated rubber bearings used to mitigate seismic damage.…”
Section: Introductionmentioning
confidence: 99%